PELATIHAN PENULISAN CERITA PENDEK DALAM BLOG DI SMK UNITOMO - Widayati, Wahyu; Andharu, Devito; Fadillah, Muhammad Reza Ishadi; Sumartono; Martono, Budi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The partner for this community service activity is SMK Unitomo which is located at Jl. Semolowaru No 84, Surabaya, East Java. The principal of SMK Unitomo is trying to provide short story writing training in blogs for female students at the school. So the partner problems, in this case SMK Unitomo, are: 1) Students' understanding of short stories; 2) Students do not have insight and knowledge regarding writing short stories in blogs, so they need training regarding how to write short stories in blogs. The short-term goal of community service activities is to increase students' knowledge and abilities by providing training on short story writing material on blogs. Apart from that, it also develops links and matches between Dr. Soetomo University and SMK Unitomo. The implementation method used in the community activity program includes 1) training, there are two stages of training, namely, training on short story writing material in blogs; 2) training in writing short stories in blogs. The results of this community service activity are: 1) There are significant differences before and after the training, before and after the concept of writing short stories was explained, this can be seen from the ability of female students to understand how to write short stories in blogs; 2) During the training process for writing short stories in blogs, partners and the service team work together so that the specified targets can be achieved well.